Sodium Salicylate Mediated Ionic Liquid Based Catanionic Coacervates as Membrane‐Free Microreactors for the Selective Sequestration of Dyes and Curcumin. Issue 3 (26th November 2019) - Shah, Ankit; Kuddushi, Muzammil; Ray, Debes; Aswal, Vinod K; Malek, Naved I.
Abstract: Designing artificial protocells to sequester the biomolecules within its compartments is a challenging task and can be achieved through the use of surfactant‐based coacervates. Surfactant structures could be tailored to achieve the highest sequestration through coacervate droplets, irrespective of the polarity, charge and type of the analytes. Herein, we designed a morpholinium‐based ester‐functionalized ionic‐liquid‐based surfactant (ILBS) with a higher surface activity than its analogous conventional surfactant to form complex catanionic coacervates over the broad range of sodium salicylate (NaSal) concentrations. The spherically shaped micellar aggregates of the investigated ILBS are transformed into cylindrical shapes and again in the spherically shaped micellar aggregates depending on the NaSal concentration, which forms the coacervate droplets. The complex catanionic coacervates have been studied for their stability in the presence of mono and divalent cations, pH, temperature, viscosity and with respect to time. The microfluidic channel of 100 μm internal diameter was designed to obtain coacervate droplets with a maximum size of 100 μm. The coacervates were designed based on the NaSal concentration; cationic, neutral and anionic to exhibit selective and non‐selective encapsulation of the model charged dyes. We speculate that the strategically designed coacervate droplets could mimic membrane‐free protocells, which are applicable in multiple biomimetic operations. Abstract : Nature mimic : Complex catanionic coacervates were designed using a functionalized ionic liquid based surfactant and sodium salicylate. The stable uniform‐sized coacervates were obtained through a microfluidic channel which shows selective and non‐selective encapsulation of the model charged dyes. The strategically designed coacervate droplets could be used as mimics of membrane‐free protocells.